Effects of Diurnal and Ontogenetic Variability on Essential Oil Composition of Oregano (Origanum vulgare var. hirtum) - GUMUSCU, AHMET; IPEK, ARIF; O. SARIHAN, ERCUMENT; GURBUZ, BILAL; DEMIR KAYA, M.; ARSLAN, NESET (Asian Journal of Chemistry, 2010)
This study was carried out to determine the effects of diurnal and stage of harvesting on the essential oil components of oregano (Origanum vulgare var. hirtum). The samples were collected at three different stages of flowering (before and after flowering) and six different times (06:00, 09:00, 12:00, 15:00, 18:00 and 21:00 h) with drying under shade or sunshine. Essential oil was obtained by hydrodistillation method and analyzed with GC-MS. Results showed that the main compound of O. vulgare var. hirtum was thymol. The harvest stage affected the compounds of essential oil such that p-cymene increased at full flowering while γ-terpinene decreased. Drying methods and harvesting time showed a minor effect on volatile compounds. The highest variation in composition of essential oil in relation to harvest stage was determined in p-cymene and γ-terpinene. It was concluded that the harvest stage along with drying under shade should be firstly considered.